Assessing the quality of patient handoffs at care transitions. Issue 6 (25th September 2012) - Manser, Tanja; Foster, Simon; Gisin, Stefan; Jaeckel, Dalit; Ummenhofer, Wolfgang
Abstract : Background: Effective handoff practices (ie, mechanisms for transferring information, responsibility and authority) are critical to ensure continuity of care and patient safety. Objective: This study aimed to develop a rating tool (self-rating and external rating) for handoff quality that goes beyond mere information transfer. Methods: The rating tool was piloted during 126 patient handoffs performed in three different clinical settings in a tertiary care hospital: (1) paramedic to emergency room staff, (2) anaesthesia care provider to postanaesthesia care unit (PACU) and (3) PACU nurse to ward nurse. Results: We identified three factors (information transfer, shared understanding, working atmosphere) predicting handoff quality. Conclusions: This study provides insights into the multidimensional concept of handoff quality. Our rating tool is feasible and comprehensive by including not only characteristics of the information process but also aspects of teamwork and, thus, provides an important tool for future research on patient handoff.